Implementasi Sistem Monitoring Gas dengan Arduino Mega2560 dan Sensor Turbin Studi Kasus PT. Perusahaan Gas Negara, Tbk - Andi Mohammad Rizki; Sabriansyah Rizqika Akbar; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The main component in the gas detection system is the Flow Computer which functions as a compensating computer of the passing gas stream. In its implementation, Flow Computer requires several sensors to read the required values on subsequent compensation. Generally are temperature sensors, pressure, and gas flow. In this research will be analyzed how data acquisition capability applied to gas detection system using Arduino Mega. Arduino Mega is a microcontroller that has the capability of general purpose (many functions). By using Arduino Mega, the author will try to replace the Flow Computer function with a microcontroller. In the hope of delivering good results as comparison and solution problems for data acquisition. The passing gas flow is read using a turbine sensor. This sensor successfully read the sensor value with a range of values 20-30 mL / s. Testing using DC 1200 rpm motor. The communication module successfully performs the exact communication switch and the value sent by each communication module does not differ remotely. Differences occur due to changes in time and conditions within the gas pipeline, but the value does not change significantly. This shows that using either Ethernet or GSM communications module (Global System for Mobile Communications), the system can provide the sensor value appropriately.